2022
DOI: 10.3390/antiox11102055
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Polyphenol Wine Metabolites Oppose Oxidative Stress and Upregulate Nrf2/ARE Pathway

Abstract: Moderate wine consumption has been associated with several benefits to human health due to its high polyphenol content. In this study, we investigated whether polyphenols contained in a particular red wine, rich in polyphenols, can pass the cell membrane and switch the oxidant/antioxidant balance toward an antioxidant pattern of THP-1 cells and human cardiomyocytes through a gene regulatory system. First, we identified which metabolite polyphenols present in red wine extract cross cell membranes and may be res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Wine extracts abundant in polyphenols effectively reduced ROS levels induced by tertbutyl hydroperoxide in a dose-dependent manner. Further study indicated that this reduction was attributed to the activation of the Nrf2-ARE pathway, an essential antioxidant defense system, as evidenced by the increased nuclear Nrf2 in cells subjected to oxidative stress [79]. These studies suggested that the change in phytochemical content through fermentation is an important factor that can demonstrate antioxidant effects through the scavenging of ROS.…”
Section: Discussionmentioning
confidence: 88%
“…Wine extracts abundant in polyphenols effectively reduced ROS levels induced by tertbutyl hydroperoxide in a dose-dependent manner. Further study indicated that this reduction was attributed to the activation of the Nrf2-ARE pathway, an essential antioxidant defense system, as evidenced by the increased nuclear Nrf2 in cells subjected to oxidative stress [79]. These studies suggested that the change in phytochemical content through fermentation is an important factor that can demonstrate antioxidant effects through the scavenging of ROS.…”
Section: Discussionmentioning
confidence: 88%
“…The authors concluded that the effects of the extract would be mediated, in part, by an increase in the activation of cyclic AMP response element-binding, which controls the induction of antioxidant genes and key pro-survival proteins such as brain-derived neurotrophic factor and B-cell lymphoma-2, among others [72]. The increase in GSH levels in parallel to the decrease in GSSG levels after the polyphenol treatment could be not only the result of the recovered GR but also because of the activation of GSH synthesis induced by the Nrf2 pathway [83]. Moreover, the decreased levels of MnSOD in old animals were also recovered after the administration of polyphenolic compounds, which could be related to an improvement in mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…The protective role of phytochemicals may be associated with their antioxidant and anti-inflammatory activities [ 9 , 10 ], since the overproduction of oxidants (reactive oxygen species and reactive nitrogen species) in the human body is involved in the pathogenesis of many chronic diseases, cancer and aging [ 11 , 12 , 13 , 14 ]. In addition, phytochemicals can regulate the expression and transcription of multiple antioxidant-related genes, thereby modulating the activity of antioxidant enzymes and antioxidants, such as glutathione, to counteract oxidative stress [ 2 , 12 , 15 , 16 , 17 ].…”
mentioning
confidence: 99%
“…In the following paper, Stranieri et al [ 17 ] evaluated whether polyphenols contained in a peculiar red wine, made from grapes and winemaking techniques designed to achieve a high content of polyphenols, can cross cell membranes and switch the oxidant/antioxidant balance toward an antioxidant pattern by means of a gene regulatory system. First, wine and the cell extracts were analysed with an untargeted metabolomics approach based on ultraperformance liquid chromatography-electrospray ionization-mass spectrometry.…”
mentioning
confidence: 99%